Analysis of oral cancer carcinogens in repeatedly heated cooking oils - Vidhant Krishna Nambiar; Vidya Mudliar; Inosi Salababa (Heliyon)
Background: The consumption of fried food has assimilated itself as a part of food culture globally. Therefore, it is important to know the toxigenicity of cooking oils used when exposed to high temperatures. The incidence of oral cancer in recent years has been on the rise; ninety percent of the cancers present in the oral cavity are squamous cell carcinoma with multiple major contributing lifestyle factors such well as the presence of the human papilloma virus. Not all mechanisms of carcinogenesis are fully understood and are complex. Furthermore, most cooking oil manufacturers do not provide recommended cooking temperatures on their product labels. Instead, they typically advise storing oils away from direct sunlight and at room temperature, leaving consumers unaware of the safe usage lim-its during cooking. Objective: This study was conducted to analyze repeated cooking oils available in Suva, Fiji for harmful levels of genotoxic carcinogens. Methodology: Six types of cooking oils (soya bean oil, olive oil, mustard oil, coconut oil, canola oil and sunflower oil) were analyzed for the presence of genotoxic carcinogens. The test group (T0-3) of oils were heated to 190 °C and tested for the presence of carcinogens using Gas chromatography Mass Spectroscopy after 1.5 h at recommended temperature (T0), reheated to 190 °C and tested after 1 h (T1), reheated to 190 °C and tested after 3 h (T2) and reheated to 190 °C and tested after 6 h (T3). The control group of oils were not heated and stored at recommended temperature before testing. Results: The concentrations of Benzo[a]pyrene and Glycidol detected in the cooking oils tested were not significant, as they remained below 2 μg/kg. However, two measurable peaks in 3-monochloropropanediol (3-MCPD) were detected in olive oil (115.6 ng/ml) and Soya bean oil (117.2 ng/ml). Conclusion: Elevated 3-MCPD levels were found in Soya bean and olive reheated cooking oils exceeding tolerable daily intake levels and indicating potential health risks. Future research should evaluate the carcinogenic potential of cooking oils in real-world settings, such as fast-food establishments. This could inform public health policies on safer oil usage practices and raise consumer awareness about the risks of consuming foods cooked with overheated or reused oils.